A Computational approach to screen, predict and annotate human and chimpanzee PHEX intronic miRNAs, their gene targets, and regulatory interaction networks. (June 2022) - Ambrose, Jenifer Mallavarpu; Anand, Daniel Alex; Kullappan, Malathi; Hussain, Sardar; James, Kavin Mozhi; Sreekandan, Radhika Nalinakumari; Suga, Sumetha Suga Deiva; Kamaraj, Devakumar; Veeraraghavan, Vishnu Priya; Mohan, Surapaneni Krishna
Abstract: The knowledge of what separates us genetically from our less-evolved relatives is crucial for gaining new biomedical insight about the human-chimpanzee relatedness that could influence the development of new treatments and diagnostic aids for various ailments. Especially, more than 300 diseases have been mapped to the X chromosome, which has unique and complicated characteristics than other chromosomes in the human genome. Although the genomes of humans and chimpanzees share 99% similarity, significant differences exist between the two species in their non-coding intronic regions. Therefore, this evolutionary-based genome annotation study attempted to computationally compare, contrast, and annotate the homologous miRNAs and their gene regulatory mechanisms in the intronic regions of the PHEX gene on the human X chromosome of the two species. From our results, we identified a total of 1296 human miRNAs and 46, 957 gene targets. Similarly, 30, 563 targets of homologous chimp miRNAs were predicted. miRNAs like hsa-miR-17–5p showed a maximum number of interactions while miRNAs like hsa-miR-107 with the least number of interactions in the human/chimp gene networks. A few top-ranked miRNAs such as hsa-miR-24, hsa-miR-145, hsa-miR-34a, and hsa-miR-378 were observed to be common between the two genera. The cooperativity and multiplicity of certain miRNAs were predicted to regulate the expression of diverse cancer-associated genes such as Cyclin D1, Notch1, CDK-6, E2F3, ALK4, CKDN2A, DHFR, and MAPK14. Nevertheless, further in vitro and in vivo experimental validations of these gene candidates are required before they could be used as potential diagnostic markers and drug targets. Graphical Abstract: ga1 Highlights: Non-coding intronic miRNAs of human and chimp PHEX gene were screened based on sequence homology. The complex regulatory interaction networks of the miRNA gene targets were delineated by comparative genomics approach. For the 1296 miRNAs identified, 46, 957 human miRNAs gene targets and 30, 563 chimp miRNA gene targets were predicted. Predicted miRNAs are known to regulate the expression of cancer-causing genes like CCND1, Notch1, CKDN2A, DHFR, and MAPK14. Multiplicity and cooperative signal integration of gene targets drive miRNA-mediated gene expression.